Building Integrated Photovoltaics (BIPV) in Line with Historic Buildings and Their Heritage Protection. (June 2019) - Novak, E; Vcelak, J
Abstract: Historic buildings are often classified as highly energy-intensive buildings with low energy efficiency. Thanks to their overall percentage share in the European real estate market, it is important to focus on these dwellings with an innovative approach and functional, sensitive aesthetic solutions, thus significantly reducing their energy intensity, increasing their energy efficiency and improving the indoor living conditions. At the same time, it will greatly increase the chance to meet the new energy and emission targets currently proposed by the European Commission.